The moderating effect of political connection on the relationship between non-audit services and accounting quality: Evidence from an emerging market - Arumega Zarefar; Nurul Azlin Azmi; Wan Adibah Wan Ismail; Khairul Anuar Kamarudin (Cogent Economics & Finance, 2023)
This study investigates whether the provision of non-audit services (NAS) is associated with accounting quality and whether political connection moderates the relationship between the NAS and accounting quality. The sample includes 2,245 firm-year observations from Malaysia during the period 2013-2017. This study uses the absolute value of discretionary accruals to measure accounting quality. We find that provision of high NAS leads to low accounting quality, exhibited by high discretionary accruals. We also find that politically connected (PCON) firms show higher discretionary accruals than non-PCON firms. However, the PCON firms weaken the positive relationship between NAS on discretionary accruals suggesting a substitutive role of political connections in determining the effect of NAS on accounting quality. We further document a non-linear association between NAS and discretionary accruals, whereby the provision of NAS would lead to low discretionary accruals after an optimal point. Therefore, regulators need to weigh the costs and benefits of regulating NAS and consider the moderating effects of PCON firms and the non-linear effect of NAS. This study adds to the limited, albeit substantial, evidence on the joint effect of PCON firms and NAS on accounting quality.
Keywords: G18; M41; M42; 330; accounting quality; discretionary accruals; non-audit services; political connection